Factorize the Trinomial ax Square Plus bx Plus c
Factorize the trinomial ax square plus bx plus c means ax
^{2} + bx + c.
In order to factorize the expression ax
^{2} + bx + c, we have to find two numbers m and n, such that m + n = b and m × n = ac.
That is we split b into
two parts m and n whereas sum m and n = b and product m and n = ac.
Solved examples to factorize the
trinomial ax square plus bx
plus c (ax^2 + bx + c):
1. Resolve into factors:
(i) 2x^{2} + 9x + 10
Solution:
The given expression is 2x
^{2} + 9x + 10.
Find two numbers whose sum = 9 and product = (2 × 10) = 20.
Clearly, such numbers are 5 and 4.
Therefore, 2x
^{2} + 9x + 10 = 2x
^{2} + 5x + 4x + 10
= x(2x + 5) + 2(2x + 5)
= (2x
+ 5)(x + 2).
(ii) 6x
^{2} + 7x - 3
Solution:
The given expression is 6x
^{2} + 7x - 3.
Find two numbers whose sum = 7 and product = 6 × (-3) = -18.
Clearly, such numbers are 9 and -2.
Therefore, 6x
^{2} + 7x - 3 = 6x
^{2} + 9x - 2x - 3
= 3x (2x + 3) -1 (2x + 3)
= (2x + 3)(3x - 1).
2. Factorize the trinomial:
(i) 2m
^{2} +7m + 3
Solution:
The given expression is 2m
^{2} +7m + 3.
Here, the two numbers a and b are such that their sum x + y =7 and their product x × y = 3 × 2 i.e., x × y = 6
Such numbers are 1 to 6
Now, splitting the middle term 7m of the given expression 2m
^{2} + 7m + 3 we get,
= 2m
^{2} + 1m + 6m + 3
= m(2m + 1) + 3(2m +
1)
= (2m +1)(m + 3)
(ii) 3x
^{2} - 4x - 4
Solution:
The given expression is 3x
^{2} - 4x - 4.
Find two numbers whose sum = -4 and product = 3 × (-4) = -12.
Clearly, such numbers are -6 and 2.
Therefore, 3x
^{2} - 4x - 4 = 3x
^{2} - 6x + 2x - 4
= 3x(x - 2) +2(x - 2)
= (x - 2)(3x + 2).
`
8th Grade Math Practice
From Factorize the Trinomial ax Square Plus bx Plus c to HOME PAGE
Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.